Impact of Palm Oil Plantation Expansion on Lowland Paddy Socio-Economic Situation in Ogan Komering Ilir Regency - Serly Novita Sari; Fachrurrozie Sjarkowi; Dessy Adriani; Maryadi Maryadi (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2021)
In the wetlands, especially peatlands, there are extensive developments and an increasing number of oil palm plantation companies. One of them is the issue of crop failure and crop failure that Ogan Komering Ilir lebak farmers had experienced during the rice season. The purpose of the study is to determine the influence of the expansion of oil palm plantations on the region's micro and macro levels. In order to have a better understanding of the farmers' perspective, farmers samples were gathered from 10 percent of the total population of 721 homes in Srigeni Baru and Mariana villages. The findings show that there is no reason for any party to view the presence of a plantation company around a small farming community in a bad manner. Communities and villages concerned about fire, palm oil plantation companies, and even rural harmony can be developed until it is fostered, for example, under the coordination of the BUKD (Badan Usaha Kemitraan Desa), which actively promotes village prosperity.